Writing analytically - Rosenwasser, David; Stephen, Jill (Australia : Cengage, 2019)
Learning to write well requires learning to use writing as a tool to think well - and this book shows you how. Writing Analytically leads you through the process of analysis and synthesis and helps you to generate original, well-developed ideas. Whether you're already a confident writer or someone who feels stranded amidst your notes and sources - waiting for the light bulb of inspiration to rescue you - this book will help you improve your skills. It's built on a series of tools for thinking that proceed step-by-step. Applying the tools will enable you to see more and arrive at better ideas about whatever you're analyzing. You'll learn to determine which details are important in your subject, how to go about figuring out why they are important, and most important, how to talk and write about what they mean. -- From amazon.com.
Includes index.
Keywords: English language -- Rhetoric; Critical thinking; Academic writing; Interdisciplinary approach in education; Academic writing; Critical thinking; English language -- Rhetoric; Interdisciplinary approach in education; Informational works